Opinions towards Companion Animals and Their Welfare: A Survey of Croatian Veterinary Students - Tomislav Mikuš; Mario Ostović; Ivana Sabolek; Kristina Matković; Željko Pavičić; Ornella Mikuš; Željka Mesić (Animals, 2020)
This survey was the first one investigating opinions of veterinary students in Croatia towards companion animals and their welfare, with special reference to dogs and cats as the most popular companion animals in the European Union. The study included students of all six years of the integrated undergraduate and graduate veterinary medicine study programme in Croatia. First-year students were surveyed twice, before and after having attended the course on animal welfare. Student opinions were assessed on the basis of their mean responses to five-point Likert scale questions and frequency of responses to Yes/No/I do not know questions and ratio scale questions. Study results revealed students to have strongly positive opinions towards companion animals and their welfare. The majority of student statements did not differ significantly between the first and sixth study years or before and after having attended the animal welfare course in the first study year, mostly yielding a straight, non-fluctuating line. Students were not sure whether welfare of companion dogs and cats was compromised. Study results pointed to reliable and reasonable opinions of veterinary medicine students in Croatia towards companion animals and their welfare, as well as to the welfare issues these species may be facing nowadays.